The effect of TiN coating on stress distribution in carbide cutting inserts in treatment of austenitic stainless steels - A. M. Lasitsa; V. G. Churankin; T. A. Churankina; R. O. Dzivulskiy (Омский научный вестник)
The article discusses the stress distribution on a cutting insert made of WC 92 % + Сo 8 % during processing of austenitic stainless steel. The calculation of the components of the cutting force is performed, the finite element method is used to calculate the stresses and displacements of the material of the triangular cutting insert TPUN 160338. It is shown that the resulting stresses exceed the yield strength of the material and stress relaxation occurs in a cobalt bond. The presence of a TiN coating leads to a more uniform stress distribution and reduces stresses to values not exceeding the yield strength.